Uttar Pradesh zamindari abolition and land reforms act, 1950 together with U.P. land revenue act, 1901 (Allahabad Universal law, 2023)
Universal's Bare Act Uttar Pradesh Zamindari Abolition And Land Reforms Act,1950 Together With U.P Land Revenue, 1901
Keywords: Law; Land reforms; Property law; Bare act